Pengaruh Pemberdayaan Psikologi dan Kecerdasan Emosional Terhadap Sikap Karier Pegawai Bank Mandiri Bengkulu - Kurniawan Kurniawan; Slamet Widodo; Syamsul Bachri (Student Journal of Business and Management, 2021)
The study aimed to assess whether the psychological empowerment and the emotional intelligence influenced the protean career attitudes. It, then, researched the clerical employees who worked at ‘Bank Mandiri’ in the area of Bengkulu with some criteria : teller, customer service, general affair and micro loan. Data were collected using a survey questionnaire which was distributed through a link: https://forms.gle/k8DgqoKEUnaNFchq7. One hundred and eighty nine   surveys were gathered and the data were analysed employing a multiple regression analysis. The results showed that the psychological empowerment and the emotional intelligence variables together influenced positively and significantly the career attitudes. It means that the higher the psychological empowerment and the emotional intelligence, the more positive the protean career attitudes are. Individually, the psychological empowerment had a positive and significant effect on the protean career attitudes; and the emotional intelligence had also a positive and significant effect on the protean career attitudes. The result reflected that empowering employees in running the bank would shape the employees’ emotional intelligence and then gave the positive attitude to the employees for their career progression. The employees felt that they contributed to the success of the bank trough their work so they would improve their skills and build a positive emotion to make their own decisions. The protean employee is involved in benefiting others. They tend towards learning and development and have the adaptability to accept change that helps them achieve organizational goals. This protean career attitude generates benefits for employees and Bank Mandiri in Bengkulu Area